(untitled) (Journal of Science and Technology, 2016)
This study was carried out to assess the contribution of yam intercrops in the continued infestation of yam tubers with S. bradys. Seven main intercrops of yam and two cowpea varieties were used for the study. The cowpea varieties were used as a check because yams were dormant at the time of the study. S. bradys-infested yam tubers bought from the Kumasi Central Market were used as inoculum. The modified Baermann funnel method for nematode extraction was used. Based on the number of juveniles and adults of S. bradys recovered from the root tissues, cowpea, tomato, okra, cassava and sorghum were found to be alternative hosts of the nematode. However, cowpea and tomato were very good alternative hosts. Maize, melon and chilli pepper were non-hosts. Nematode multiplication in roots showed that S. bradys could survive endoparasitically in the roots of other crops. The effect of nematode numbers on the state of the roots of the intercrops screened revealed that generally, necrosis increased with increasing number of the nematode. Following this study, it is recommended that maize, melon and chilli pepper could be intercropped with yam.